2022
DOI: 10.1371/journal.pone.0276057
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for partnering with Ryan White Case Managers to create equitable opportunities for people with HIV to participate in research

Abstract: Many research studies focus on recruitment from one or few HIV clinics or internet-engaged populations, but this may result in inequitable representation of people with HIV (PWH), across the rural/urban/suburban continuum. Ryan White Case Managers (RWCM) meet regularly with PWH, potentially positioning them as partners in gathering research-related data from diverse groups of low-income, marginalized, PWH. Yet, data collection in partnership with RWCM, particularly over large geographic areas, has been under-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Klassen et al [ 40 ] suggested that regular contact with health care facilities and face-to-face interactions with trusted sources such as health care providers may be critical in successfully recruiting participants who are HIV positive. Another study found success in partnering with Ryan White Case Managers to collect data from people with HIV, especially those who are hard to reach, disenfranchised, or underrepresented [ 41 ]. Leveraging the relationship between health care providers and youth living with HIV may yield a more specific, targeted, and efficient avenue to recruit a diverse pool of eligible participants, especially using the HRSA Ryan White HIV/AIDS Program’s comprehensive system of care and treatment [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Klassen et al [ 40 ] suggested that regular contact with health care facilities and face-to-face interactions with trusted sources such as health care providers may be critical in successfully recruiting participants who are HIV positive. Another study found success in partnering with Ryan White Case Managers to collect data from people with HIV, especially those who are hard to reach, disenfranchised, or underrepresented [ 41 ]. Leveraging the relationship between health care providers and youth living with HIV may yield a more specific, targeted, and efficient avenue to recruit a diverse pool of eligible participants, especially using the HRSA Ryan White HIV/AIDS Program’s comprehensive system of care and treatment [ 29 ].…”
Section: Discussionmentioning
confidence: 99%